Knowledge, attitudes, and practices related to antibiotic use and antibiotic resistance among poultry farmers in urban and peri-urban areas of Ouagadougou, Burkina Faso - Sawadogo, A.; Kagambèga, A.; Moodley, Arshnee; Ouédraogo, A.A.; Barro, N.; Dione, Michel M. (MDPI, 2023)
Increased use of antibiotics in livestock is a public health concern, as it poses risks of antibiotic residues and antibiotic-resistant pathogens entering the food chains and infecting humans. A cross-sectional survey was conducted on 216 poultry farms to study knowledge, attitudes and practices of poultry farmers on the use of antibiotics in urban and peri-urban areas of Ouagadougou. Results show that only 17.13% (37/216) of farmers attended training on poultry production. Majority of farmers—85.65% (185/216) were not knowledgeable about the rational use of antibiotics. When there was a disease outbreak, 31.98% (63/197) of farmers used veterinary drugs without a prescription and 22.34% (44/197) consulted a community animal health worker. It should also be noted that 79.19% (156/197) of farmers reported using chicken meat as per normal if the bird died during or right after treatment with an antibiotic. Knowledge of rational use of antibiotics was positively influenced by a good attitude adopted by the farmer during the illness of birds and negatively influenced by disease treatment success and high level of education of the farmer. Lack of knowledge about the rational use of antibiotics including their use without a prescription are serious risk factors for the emergence of antimicrobial resistance. Awareness of farmers and other veterinary drug supply chain actors such as drug stockists and animal health workers on best practices in antimicrobial use and promotion of good biosecurity on farms are important to reduce the misuse of antibiotics.